Organic-inorganic hybrid coatings for corrosion protection of galvanized steel and electroplated ZnFe steel - Souza, M. E. P. (2005)
The development of hybrids materials by the sol-gel process has been extensively investigated in recent years. The combination a wide variety of compositions and production processes had permit the use of these materials in different applications like coatings for corrosion protection of metals and abrasion resistant coatings. In this work organic-inorganic hybrid materials have been prepared from the hydrolysis of tetraethylorthosilicate (TEOS) and silanol-terminated polidymetilmetoxysilane (PDMS) using a sol-gel process. The composition evaluated was 50% TEOS- 50% PDMS. These materials have been applied on galvanized steel and on steel electroplated with a ZnFe alloy. In order to evaluate the degradation behaviour of these coatings, electrochemical techniques were used. They consisting in the monitoring of the open-circuit potential (Ecorr), and in the realization of potentiodynamic polarization measurements of the samples, which was performed in a 3% NaCl aqueous solution. Additionally, electrochemical impedance spectroscopy (EIS) was used as a complementary technique for the evaluation of the corrosion mechanisms of the coating system. The surface of the samples, before and after the electrochemical tests, have been inspected by SEM and EDS. EIS data was fitted to an equivalent circuit from which the electrochemical parameters were obtained. Results show a good protective character of the hybrid films, when compared with uncovered specimens. The capacitance of the films increased with the immersion time, in accordance to the behaviour expected for an organic film. The overall performance of the coating systems appears to be highly dependent on the kind of metallic coating applied to the steel. Coatings applied upon galvanized steel showed larger |Z| values when compared with those applied to the electroplated steel, indicating a superior corrosion resistance of the former and a better stability throughout the immersion time.